THU0105 Effect of sirukumab on hepcidin levels and markers of anemia: Results of a phase 2B trial in patients with active rheumatoid arthritis despite methotrexate therapy. (23rd January 2014) - Toedter, G.; Sague, S.; Wu, X.; Curran, M.; Hsu, B.
Abstract : Background: Anemia of chronic inflammation is found in patients with rheumatoid arthritis (RA). Studies have found that RA patients with anemia are more likely to have more severe joint damage. 1 Hepcidin is a peptide hormone that regulates iron homeostasis, is elevated in anemic conditions, and is up-regulated by interleukin-6 (IL-6). IL-6 is also elevated in RA. Sirukumab (CNTO136), a human anti-IL-6 monoclonal antibody, was investigated for efficacy in a Phase 2b dose ranging study of patients with active RA despite concurrent methotrexate treatment. Objectives: This analysis examines if sirukumab treatment had positive effects in RA patients anemic at baseline (week 0) by reducing hepcidin and increasing hemoglobin through week 12 of treatment. Methods: Serum samples collected in the Ph2b study at week 0, day 5, week 2, and the pre-specified week 12 primary endpoint were analyzed for hepcidin, hemoglobin, and anemia-related markers (ferritin, iron, total iron biding capacity, unsaturated iron bind capacity). Patients were treated with SC placebo (PBO; n=30) or SC sirukumab 100 mg 2QW, 100 mg 4QW, 50 mg 4QW (n=30 for each arm), or 25 mg 4QW (n=31). Results: The overall ACR 50 response at week 12 to sirukumab was 24.0% (PBO 3.3%). At week 0, 5/30 (16.7%) of PBO and 37/121 (30.6%) of sirukumab-treated patients were anemic. In the anemic patients, the mean week 0 hepcidin concentrations were 25.1 ng/mL in the PBO group, and 87.4 ng/mL in the sirukumab-treated patients. At week 12, the sirukumab-treated patients mean hepcidin concentration was significantly reduced to 38.1 ng/mL (p=0.0029), while the PBO mean hepcidin concentration was unchanged (31.4 ng/mL; p=0.6250). No dose-response of sirukumab on serum hepcidin concentration was seen. Hemoglobin levels in the anemic patients increased in the sirukumab-treated patients (10.6 g/dL at week 0; 11.8 g/dL at week 12; p<0.001) but were unchanged in the PBO group (10.2 g/dL at week 0; 9.8 g/dL at week 12; p=0.6250). By week 12, no patients in the PBO group normalized hemoglobin levels, while 19 patients in the sirukumab-group normalized hemoglobin (51.4% of the week 0 anemic patients). All of the measured anemia-related markers correlated significantly with post-treatment hepcidin concentrations. There was no relationship between ACR20 or ACR50 response at week 12 and normalization of hemoglobin. Conclusions: Sirukumab was effective in reducing serum concentrations of hepcidin through week 12 of treatment. Serum hemoglobin levels in anemic patients increased significantly following sirukumab treatment, with half of the patients normalizing hemoglobin levels. This indicates that in addition to demonstrating efficacy, treatment of RA patients with sirukumab may be effective in reversing inflammation-related anemia. References: Peeters HR, et al. Ann Rheum Dis. 1996;55:162-168 Disclosure of Interest: G. Toedter Employee of: Janssen Research & Development, LLC, S. Sague Employee of: Janssen Research & Development, LLC, X. Wu Employee of: Janssen Research & Development, LLC, M. Curran Employee of: Janssen Research & Development, LLC, B. Hsu Employee of: Janssen Research & Development, LLC